Implementation Of The Stunting Prevention Policy As One Of Themes Of Government Science Study: A Bibliometric Review - Tri Kisowo Jumino; Ika Sartika (Syntax Idea)
Stunting remains a critical public health issue and a key focus of government policy implementation studies. This research aims to analyze the development of studies on the implementation of stunting prevention policies within the field of government science over the past decade. Using a systematic literature review approach, this study employs bibliometric analysis with data retrieved from Google Scholar. The analysis was conducted using Publish or Perish and VOSviewer, reviewing 100 studies, of which 67 were selected and categorized into 9 nodes within 3 clusters, resulting in 25 links and a total link strength of 88. Despite covering studies from 2014 to 2024, findings indicate that research on the implementation of stunting prevention policies has been most active during 2022–2023. The study highlights key trends and gaps in existing literature, providing insights into areas that have been extensively explored and those that require further investigation. As an implication, future research is encouraged to explore underexamined topics such as stunting prevention strategies, stunting management, and specific case studies on stunting reduction efforts. This study contributes to the academic discourse by mapping research trends and providing direction for future scholarly inquiry on the implementation of stunting prevention policies.